From explosive vent opening to effusive outpouring : mineral constraints on magma dynamics and timescales at paricutin monogenetic volcano - Larrea, Patricia (2021)
Paricutin volcano is the youngest monogenetic cone of the Michoacán–Guanajuato volcanic field (Mexico), with an excellent historical eruption record from February 1943 to March 1952. The magma emitted during the 9 years of activity was compositionally zoned from basaltic andesite to andesite. This eruption has been considered a classic example of magma differentiation controlled by crustal assimilation combined with fractional crystallization. However, a recent geochemical study of the eruption products points to mantle source heterogeneity and fractional crystallization as the key processes involved in the compositional variability of the magmas. Here we present a detailed petrological characterization of the minerals [olivine, plagioclase, pyroxene, Cr-spinel, and (Ti-)magnetite] to shed light on the processes that led to the chemical evolution of the eruptive products. Our sample set includes the early tephra from the first weeks or months of eruption and the whole sequence of lava flows that followed. The mineral assemblage, their texture, and chemical composition show a systematic evolution between the products from the opening of the explosive vent to the effusive stage. The early tephra are basaltic andesites with oscillatory-zoned olivine and plagioclase, zoned Cr-spinel, and rare pyroxene xenocrysts. In contrast, later erupted tephra and post-January 1944 lavas are basaltic andesites and andesites with normally zoned olivine, Cr-spinel inclusions in equilibrium with the host olivine, and frequent orthopyroxene (after December 1947) with minor chemical zoning. Mineral chemistry data and olivine diffusion timescales, together with whole-rock geochemistry, suggest a convective magma regime with large temperature and oxygen fugacity gradients characterized by short timescales (few days) during the opening stage, followed by a steadier magma regime with longer timescales (few months) and including periodic magma recharge, mixing, and fractional crystallization. In addition, the mineralogical evidence we have gathered does not support considerable crustal assimilation at Paricutin. This study shows that monogenetic eruptions are far from being geochemically simple, and instead involve multiple magma batches with complex storage and mixing stages before eruption.